Regulator of calcineurin 1 differentially regulates TLR-dependent MyD88 and TRIF signaling pathways - Pang, Zheng (PLoS One, 2018)
Toll-like receptors (TLRs) recognize the conserved molecular patterns in microorganisms and trigger myeloid differentiation primary response 88 (MyD88) and/or TIR-domain-containing adapter-inducing interferon-β (TRIF) pathways that are critical for host defense against microbial infection. However, the molecular mechanisms that govern TLR signaling remain incompletely understood. Regulator of calcineurin-1 (RCAN1), a small evolutionarily conserved protein that inhibits calcineurin phosphatase activity, suppresses inflammation during Pseudomonas aeruginosa infection. Here, we define the roles for RCAN1 in P. aeruginosa lipopolysaccharide (LPS)-activated TLR4 signaling. We compared the effects of P. aeruginosa LPS challenge on bone marrow-derived macrophages from both wild-type and RCAN1-deficient mice and found that RCAN1 deficiency increased the MyD88-NF-κB-mediated cytokine production (IL-6, TNF and MIP-2), whereas TRIF-interferon-stimulated response elements (ISRE)-mediated cytokine production (IFNβ, RANTES and IP-10) was suppressed. RCAN1 deficiency caused increased IκBα phosphorylation and NF-κB activity in the MyD88-dependent pathway, but impaired ISRE activation and reduced IRF7 expression in the TRIF-dependent pathway. Complementary studies of a mouse model of P. aeruginosa LPS-induced acute pneumonia confirmed that RCAN1-deficient mice displayed greatly enhanced NF-κB activity and MyD88-NF-κB-mediated cytokine production, which correlated with enhanced pulmonary infiltration of neutrophils. By contrast, RCAN1 deficiency had little effect on the TRIF pathway in vivo. These findings demonstrate a novel regulatory role of RCAN1 in TLR signaling, which differentially regulates MyD88 and TRIF pathways.